Les diplômés en langue arabe au sein de l'élite sénégalaise : du symbolique à l'académique - Hamidou Dia (Les éditions de la Maison des sciences de l'Homme, 2015)
Senegal has been training and sending abroad Arab-speaking graduates at least since independance. Those Arab-speaking graduates acquired their school and academic qualifications in a broad range of national and international contexts. A lot of them have been kept outside of state institutions, which makes it difficult for them to participate in public life. An emphasis on victimization has developed from various bodies in the country. But a sociohistorical analysis of their condition, especially within the senegalese higher education system, adds nuance to this rhetoric. The article shows the ongoing social change that has been taking place for close to twenty years: Arab-speaking graduates emerge in university, take part in shaping the constant development of academic services, build alliances with other spheres of influence in contemporary Senegal, state their vision of the country, constitute lobbies, gradually assert themselves as a confident section of the senegalese elite. The article exemplifies what made this transformation possible.